How Can We Make TVET Institute Center of Excellence? - Lamichhane, Ramhari (Journal of Technical and Vocational Education and Training, 2021)
A country needs to ensure proper human resource management for its socio-economic development, where the role of TVET is significant. Enhancing quality of TVET should therefore be one of the priorities. In line with other education programs, TVET programs need a paradigm shift to make our youth fit for global market with adequate competencies for global competitiveness. The institute with quality managed center of excellence only can offer competencies for the global competitiveness. Center of excellence (CoE) institute is known as having quality management system (QMS) in place, accredited by national and international body, high ratings perception of stakeholders and reputed image in the society. There are ample of practices by many countries on CoE. The criteria varies from one another; however, the major thrust areas are the same or similar. Institute, industries, students, parents and country can get direct benefits from the establishment of CoEs in the TVET system. There should be policy intervention, implementation system and commitment from leadership to establish a well functioned CoE.